Microstructural morphology and crystallographic orientation characteristics of as-cast alloys Ti1.8(VFe)CrNi0.2 + x wt% LaNi5 (x = 2.5, 4, 5, 6, 10). (21st September 2020) - Cui, Junjie; Liu, Xiangdong; Lü, Kai; Lu, Yan; Liu, Qi
Abstract: The performances of hydrogen alloy strongly depend on its microstructural characteristics. And the microstructural morphology, crystallographic orientation, and elemental distribution in alloys represent the internal structural features of crystals. In this present work, the multi-component Ti–V–Cr-based alloys Ti1.8 (VFe)CrNi0.2  +  x wt.% LaNi5 ( x  = 2.5, 4, 5, 6, 10) were prepared by the two-step re-melting method and the variation of microstructural morphology, lattice constants which reflect intrinsic characteristics of crystals, and microstrain in the alloys containing a different content of LaNi5 were investigated. The results shows that the crystalline diameters in the solidification microstructures of the investigated specimens dropped continuously along the minor axis and the grain size increased with the increase of LaNi5 -content from 2.5 wt.% up to 5 wt.%. Meanwhile, a tendency of crystallographic orientation correlated distinctly with the close-packed [001] and [110] directions and the {110} planes appeared. Moreover, there exhibited the symbiotic relations of coherent interface between the major and minor phases. The preferential growth of elongated-grain in axial direction occurred due to decrease of lattice mismatch at the interfaces in the case of high Ti-content dissolved in the major phase. In particular, it was found that the grains of alloy containing 5 wt.% LaNi5 grew predominantly along the close-packed [001] or [110] directions and the {110} planes and the average of diameter and length of unique elongated-grain reached the minimum of 6.51 μm and maximum of 291.45 μm, respectively, for the high Ti content of 33–42%, mostly 33%, in the major phase, which induced a smallest mismatch and lattice distortion, only a misorientation angle of approximately 1.875°, determined using electron backscattered diffraction (EBSD). In addition, the evidences from the analyses of EBSD suggest that the internal microstrain in the major phase of alloy containing 5 wt.% LaNi5 slightly enlarged, represented as a largest local misorientation angle of 1.9°. It is demonstrated that there is an important influence of the content of LaNi5 on the microstructural morphology and crystallographic orientation in Ti-based alloys and it may act as a method of microstructure regulation of phases in hydrogen alloys. Graphical abstract: Image 1 Highlights: Elongated-grains of Ti1.8 (VFe)CrNi0.2 occurred with LaNi5 -content from 4 to 5 wt.%. Symbiotic relations of Ti–V–Cr-based alloys between two phases were verified. Smallest diameters were obtained due to symbiotic relations with lowest mismatch. Changes of mismatches were caused by varied Ti-content in major phase. There exhibited uniform distribution of Ti around the zones of La in major phase.